SEBUAH KARYA FEATURE WISATA DAN PERJALANAN “TABLE STORY” - Rangga Sikunantindi; Muhammad Darwinsyah (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2019)
Current feature programs broadcast on Indonesian television have begun to be of little interest to the public, because they have begun to be displaced by other television programs whose content is merely entertainment. Though the community needs various programs that are able to provide information, inspiration and education in order to provide and increase awareness of the potential of their own people. The creator of the work wants to create a program that has a lot of information, inspiration and education about culinary from both the dish and the place. This program is a culinary travel feature titled